Appraisal of national and international uterine fibroid management guidelines: a systematic review. (30th September 2021) - Amoah, A; Joseph, N; Reap, S; Quinn, SD
Abstract : Background: Guidelines standardise high‐quality evidence‐based management strategies for clinicians. Uterine fibroids are a highly prevalent condition and may exert significant morbidity. Objectives: To appraise national and international uterine fibroid guidelines using the validated AGREE‐II instrument. Selection strategy: Database search of PubMed and EMBASE from inception to October 2020 for all published English‐language uterine fibroid clinical practice guidelines. Data collection and analysis: In all, 939 abstracts were screened for eligibility by two reviewers independently. Three reviewers used the AGREE‐II instrument to assess guideline quality in six domains. Recommendations were mapped to allow a narrative synthesis regarding areas of consensus and disagreement. Main results: Eight national guidelines (AAGL, SOGC 2014, ACOG, ACR, SOGC 2019, CNGOF, ASRM and SOGC 2015) and one international guideline (RANZOG) were appraised. The highest scoring guideline was RANZOG 2001(score 56.5%). None of the guidelines met the a priori criteria for being high‐quality overall (score ≥66%). There were 166 recommendations across guidelines. There were several areas of disagreement and uncertainty. There were only three areas of consensus. Supporting evidence was not evident for many recommendations; 27.7% of recommendations were based on expert opinion only. Conclusions: There is a need for high‐quality guidelines on fibroids given their heterogeneity across individuals and the large range of treatment modalities available. There are also areas of controversy in the management of fibroids (e.g. Ulipristal acetate, power morcellation), which should also be addressed in any guidelines. Future guidelines should be methodologically robust to allow high‐quality decision‐making regarding fibroid treatments. Tweetable abstract: Current national fibroid guidelines have deficiencies in quality when appraised using the validated AGREE instrument. Tweetable abstract: Current national fibroid guidelines have deficiencies in quality when appraised using the validated AGREE instrument. Linked article This article is commented on by A Wojtaszewska, M Hirsch, pp. 365–366 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.17006 .